An investigation of harmonic energy losses due to non-linear load in laboratory power system analysis and control UniMAP - Mohd Nur Naimullah Jailani (School of Electrical System Engineering, University Malaysia Perlis, 2011)
Power quality is defined as any power problem manifested in voltage, current or frequency deviation that result in failure or misoperation of customer equipment. Harmonic in sinusoidal voltage or current which has frequencies that are integer multiples of the fundamental frequency ( frequency at which the supply system is designed to operate, normally 50 or 60H). Firstly the harmonic current and voltage were get at distribution board in laboratory Power System Analysis and Control UniMAP by using power quality analyzer.